Domestication and Foreignization Strategies in the Translation of Humorous Hadiths: An Inquiry into Translation Ideology - Agil Husein Al Munawar; Mohamad Zaka Al Farisi; Deni Ramdani (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2025)
The difficulty of translating humor that is rich in cultural and religious values poses a dilemma between preserving the authenticity of the source text or adapting it to the culture of the target audience. This challenge becomes even more significant in the translation of the Prophet's humorous hadiths, which contain messages of Islamic preaching and ethics. To address this issue, a qualitative approach was employed, involving content analysis of the humorous hadiths in the book Everything Has Its Time by Sheikh Mahmud Al-Mishri, translated by Ustadz Abdul Somad. Data analysis was conducted by identifying cultural words, classifying translation strategies according to Peter Newmark, and interpreting ideological tendencies based on Lawrence Venuti's domestication and foreignization theory. The results of the study indicate that domestication strategies, particularly descriptive equivalent, through-translation, and paraphrase, were used most frequently, while other strategies such as componential analysis, recognized translation, modulation, and shifts appeared less often. The conclusion suggests that domestication strategies contribute to achieving a balance between meaning accuracy and cultural acceptance, thereby maintaining both comprehensibility and religious values. Translators of religious humorous texts are therefore encouraged to uphold this balance so that the message of Islamic preaching remains intact and communicative.